The peculiarities of reduction of iron (III) oxides deposited on expanded graphite. Issue 2 (23rd January 2014) - Lutfullin, Marat; Shornikova, Olga; Dunaev, Alexander; Filimonov, Dmitry; Schur, Alina; Saidaminov, Makhsud; Sorokina, Natalya; Avdeev, Viktor
Abstract